2018
DOI: 10.22159/ijpps.2018v10i7.25858
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists Compliance to Practice Regulations and Good Professional Practice: A Case Study of Nigerian Community Pharmacists

Abstract: Objective: This study was designed to assess community pharmacists’ compliance to rules and regulations guiding the practice of pharmacy in Anambra state, Nigeria.Methods: The study was carried out using a mixed method. In the first phase, adapted and validated questionnaire was used to obtain demographic data and information on some practice standards. While in the second phase, the researcher interviewed the practicing pharmacists on some of the key practice standards followed by observation of the items inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This is similar to a study in South Africa, which revealed a major policy implementation gap between the national government and the participants [24]. It corresponds with a study in Anambra State, where observations and interviews conducted in the state revealed a low level of compliance with practice regulations [25]. Some Nigerian researchers that conducted a study among four states (Lagos, Ogun, Niger, and Plateau State) in Nigeria reported low compliance on disposal practices of pharmaceutical wastes.…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to a study in South Africa, which revealed a major policy implementation gap between the national government and the participants [24]. It corresponds with a study in Anambra State, where observations and interviews conducted in the state revealed a low level of compliance with practice regulations [25]. Some Nigerian researchers that conducted a study among four states (Lagos, Ogun, Niger, and Plateau State) in Nigeria reported low compliance on disposal practices of pharmaceutical wastes.…”
Section: Discussionsupporting
confidence: 88%
“…This segment suffers from the problem of information asymmetry across the different layers of regulatory and enforcement mechanisms. There is a large variance in the quality of drug regulation across states in the country, since each state having their own regulations [30]. Drug inspectors of India who are the key players in drug regulations should be made highly qualified and be well paid to bring about the dignity associated with the huge responsibility.…”
Section: Regulatory Challengesmentioning
confidence: 99%